2010
DOI: 10.1007/s12072-010-9187-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic risk factors of hepatocellular carcinoma in a rural region of Egypt

Abstract: Background Hepatocellular carcinoma (HCC) is a major health problem worldwide, including Egypt. In the recent past, HCC has become the second most prevalent cancer among men in Egypt. Since HCC has not been well studied in the rural population of Egypt, this case-control study was conducted to investigate the epidemiologic risk factors of HCC in the predominantly rural region of Gharbiah, Egypt. Methods A total of 150 cases and 150 controls matched to cases on age (±5 years) and sex were recruited from the Gha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Several studies ascertained occupation and industry information from a national supplemental pension fund, interviews, and questionnaires [44, 46, 5052]. Some studies coded occupational information using classification systems such as the International Standard Classification of Occupations and the International Standard Industrial Classification of All Economic Activities [44, 46, 50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies ascertained occupation and industry information from a national supplemental pension fund, interviews, and questionnaires [44, 46, 5052]. Some studies coded occupational information using classification systems such as the International Standard Classification of Occupations and the International Standard Industrial Classification of All Economic Activities [44, 46, 50].…”
Section: Resultsmentioning
confidence: 99%
“…Job titles were typically defined as farmer, farm worker, and farm laborer, and industries as agriculture. Although farming occupation was generally not associated with liver cancer [46, 50, 52], Schiefelbein et al (2012) showed farming vs. never employed in farming was associated with a statistically significant increased risk of HCC in Egypt (adjusted OR 2.8, 95% CI 1.1, 7.2), adjusting for HBV, anti-HCV, schistosomiasis, cirrhosis, and blood transfusion (controls were matched to cases according to age and sex) (Table 2) [51]. Pesticide exposure defined based on working in the agriculture industry in Denmark was not associated with liver cancer (Table 2) [44].…”
Section: Resultsmentioning
confidence: 99%
“…Hepatitis C virus (HCV) infects primarily hepatocytes, leads to the development of fibrosis or cirrhosis of the liver, and is a significant risk factor for the development of HCC, in a process termed as 'inflammation-fibrosis-cancer axis' deaths. In Africa, HCC is the dominant type of liver cancer (Soliman et al, 2010). HCC is the second most frequent cause of cancer incidence and mortality among men in Egypt (Lehman and Wilson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The publications highlight findings based on research with populations in the USA of Native Americans [4], Asian Indian women [5], and Arab Americans [6]. Published research from international settings also includes knowledge of human papilloma virus [7] and reliability of reproductive history recall among North African women [8]. Student publications in international training sites also have examined inflammatory breast cancer [9], bladder cancer [10], pancreatic adenocarcinoma [11], pediatric brain tumors [12], cervical cancer [13], and the concordance of plasma and tumor DNA methylation in hepatocellular carcinoma [14].…”
Section: Resultsmentioning
confidence: 99%